The importance of collecting pre- and post-intervention practice data when conducting a randomised controlled trial - Nelly Newall, & Gill Lewin and Duncan Boldy (Wound Practice and Research, 2016)
Both practice and outcomes data sets are integral to any randomised controlled trial (RCT) design and should be collected both before and after the intervention has been implemented to understand if a change has occurred as a result of the intervention. However, it is not unusual for only outcomes data to be collected. In this paper a mixed methods descriptive study, which was a discrete part of a moisturising RCT, is used to demonstrate the importance of collecting pre- and post-intervention practice data. This paper demonstrates how the descriptive study aimed to enhance the researchers’ understanding of the outcomes of the moisturising RCT by determining how practice changed within the facilities in each arm of the study. In summary, this study was designed to ensure the results from the moisturising RCT could be accurately interpreted and it was a critical, but independent component of the moisturising study.